Experimental Strength Analysis of Variable Stiffness Waffel-Grid Cylindrical Compartments. Part 1. Experimental Procedure - Degtyarev, M.A.; Danchenko, V.G.; Shapoval, A.V.; Avramov, K.V. (Проблеми машинобудування, 2019)
This paper proposes a method of the experimental study of the static stress-strain state (SSS) of the variable stiffness tail section of a launch vehicle (LV). The article summarizes the results of the experimental analysis of the static SSS of an optimized tail section body under the conditions of loading close to realistic ones. Запропоновано метод експериментального дослідження статичного напружено-деформованого стану (НДС) хвостового відсіку ракети-носія змінної жорсткості. У статті описуються результати експериментального аналізу статичного НДС оптимізованого корпусу хвостового відсіку під дією зусиль, що є наближеними до натурних. Предложен метод экспериментального исследования статического напряженно-деформированного состояния (НДС) хвостового отсека ракеты-носителя (РН) переменной жесткости. В статье описываются результаты экспериментального анализа статического НДС оптимизированного корпуса хвостового отсека в условиях нагружения, близкого к натурному.